Death education and photovoice at school: A workshop with Italian high school students. Issue 3 (16th March 2023) - Raccichini, Melania; Biancalani, Gianmarco; Franchini, Luca; Varani, Silvia; Ronconi, Lucia; Testoni, Ines
Abstract: The study shows the effects of a death education workshop with Italian high school students. Students ( N  = 416) from 10 high schools throughout Italy participated: 212 in the experimental group and 204 in the control group. Four weekly, two-hour workshops about the themes of death, with theoretical lessons and an experiential artistic activity of photovoice. Results show that the students in the experimental group showed significantly increased self-efficacy levels and existential anxiety levels did not increase after death education intervention. Educating youth about death could give them the skills to improve the management of death-related events and cope with negative emotions.